Digital Product Marketing for Digitalpreneur: Challenges and Strategies - Pramayanti, Dian Ikha; Kurnia (Yayasan Meira Visi Persada, 2025)
In an increasingly evolving digital era, digitalpreneurs face various challenges in marketing their digital products. Intense competition, changing consumer behavior, resource limitations, and the need to build brand awareness are some of the main issues encountered. This article aims to explore these challenges and provide effective solutions to address them. Proposed solutions include product differentiation, market segmentation, innovation in marketing, consumer trend monitoring, leveraging cloud technology, and utilizing high-quality content and paid advertising campaigns. By implementing the right strategies, digitalpreneurs can enhance their chances of success in marketing their digital products in an increasingly competitive market.